Social Influence Operations of the Russian Federation and Belarus in a Context of Accusations against the Polish Central PSYOPS Group of Conducting Subversive Activity in Belarus - Wiśnicki, Jarosław (Historia i Polityka, 2022)
This paper presents basic methods and measures used to conduct social influence operations, indicating their metamorphosis associated with conditions characteristic for shaping public opinion by the Russian Federation and Belarus. Furthermore, the analysis covered mechanisms of informational influence used when creating accusations directed at the Polish Central PSYOPS Group, concerning conducting subversive activities in Belarus. The emphasis is put on their comprehensive nature, enabling effective influence both on international entities, and on individual targets. A significant part of this article concerns an analysis focusing on distribution of information, as well as applied techniques, tools and communication channels, used in social influence operations. The influence and the role of mass media in shaping of awareness was presented, revealing mechanisms for creating the cognitive space.